Perancangan dan Implementasi Jaringan Hotspot Untuk Akses Internet di SMK Asta Mitra Purwodadi - Hidayat, Nuzulil, Ir. Bana Handaga, M.T., Ph.D (2016)
Making hotspot area in vocational high school of Asta Mitra of Purwodadi so necessary, given the number of students is large enough and has a high level of mobility. Internet is something that is currently much in demand, and therefore a lot of people want to get access and connect to the Internet. The high degree of mobility of people making them have a gadget that has a feature for Internet access. Education is one department that is relatively much use of the internet. It is making a school is required to have internet access. To maximize the schools, so the all citizens of school can use the internet facilities independently. The school provides the hotspots that can be used by users independently. In conducting this study, the method used is the method of simulation and implementation. To obtain the data in this research is to conduct library research, observation and interviews. The design hotspot network built in vocational of Asta Mitra of Purwodadi made in accordance with the data obtained from the analysis of the needs which will then be simulated using cisco packet tracer. Results of design have made will be implemented directly in vocational of Asta Mitra of Purwodadi. The result of this research is to design and create a new hotspot network, which intended to facilitate internet users in Asta Mitra vocational high school of Purwodadi in the accessing the Internet networks via hotspots that have been used. Hotspot network is made so that the Internet can be accessed not only from within the laboratory or in the room and use the cable alone, but is intended to allow users to access the internet from the outdoors and using personal gadget. The design and implementation will be made as simple as possible and tailored to the needs of the school, so that the school is not so difficult if developing later time.